Solid electrolyte material, preparation method thereof and solid-state battery

By adopting solid-state electrolyte material and S element doping technology with the general formula of LiaMmNnClbSc in solid-state batteries, the problem of low ion conductivity of solid-state batteries is solved, and the high conductivity and battery capacity are improved, which enhances the stability of the battery and Security.

CN119297383APending Publication Date: 2025-01-10QINGTAO (KUNSHAN) ENERGY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411439870.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The ionic conductivity of existing solid-state batteries is low, which affects their battery capacity and stability, and it is difficult for traditional preparation methods to effectively improve the conductivity.

Method used

Using the solid electrolyte material with the general formula of LiaMmNnClbSc, the chloride of LiCl, Li2S, the chloride of the first metal element and the chloride of the second metal element are mixed according to the stoichiometric ratio to form a solid electrolyte with high ionic conductivity, and the S element is used. Doping improves deformation capability and conductivity.

Benefits of technology

It significantly improves the ionic conductivity and battery capacity of solid electrolytes, extends the cycle life of the battery, and improves the safety and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297383A_ABST
    Figure CN119297383A_ABST
Patent Text Reader

Abstract

The invention provides a solid electrolyte material, a preparation method thereof and a solid-state battery, and relates to the field of batteries. The general formula of the solid electrolyte material is LiaMmNnClbSc, M is a first metal element, and N is a second metal element; 1 < a < 5, 0.3 < m + n < 2, b + 2c = a + m * d + n * e, d is the valence of the first metal element, and e is the valence of the second metal element. By blending the first metal element and the second metal element, the ionic conductivity of the solid electrolyte material is effectively improved. In addition, the deformation capacity of the solid electrolyte material can be improved through S element doping, and the solid electrolyte with high ionic conductivity can be formed through ball milling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a solid electrolyte material and a preparation method thereof, and a solid-state battery. Background Art

[0002] Solid-state batteries are energy storage elements that can store electrical energy and release it when needed. Compared with traditional liquid batteries, solid-state batteries use solid electrolytes instead of liquid or gel electrolytes for ion transmission, and have higher safety, higher energy density, faster charging speed and longer cycle life.

[0003] Solid-state electrolytes, as the medium for ion transmission in batteries, directly affect the performance and stability of solid-state batteries. Solid-state electrolytes with high ionic conductivity are crucial to improving the battery capacity of solid-state batteries. Summary of the invention

[0004] Based on this, it is necessary to provide a solid electrolyte material with high ionic conductivity and a preparation method thereof, and a solid-state battery.

[0005] In a first aspect, the present invention provides a solid electrolyte material, wherein the general formula of the solid electrolyte material is Li a M m N n Cl b S c , wherein M is the first metal element, N is the second metal element; 1<a<5, 0.3<m+n<2, b+2c=a+m×d+n×e, d is the valence of the first metal element, and e is the valence of the second metal element.

[0006] In one embodiment, m+n=1, and the value range of m is 0.3~0.7.

[0007] In one embodiment, the value range of c is 0.4~1.

[0008] In one embodiment, the first metal element includes Zr 4+ 、Ti 4+ , Hf 4+ 、Al 3+ , Y 3+ Sc 3+ 、In 3+ 、Eu 3+ One or more of .

[0009] In one embodiment, the first metal element includes Zr 4+ , Y 3+ 、In 3+ One or more of .

[0010] In one embodiment, the second metal element includes Fe 3+ 、V 3+ , Ga 3+ 、Ru 3+ , Rh 3+ 、Bi 3+ 、Au 3+ , Ir 3+ 、Re 3+ ,La 3+ 、Ce 3+ , Pr 3+ 、Nd 3+ 、Sm 3+ , Gd 3+ , Tb 3+ 、Dy 3+ 、Ho 3+ , Er 3+ 、Tm 3+ , Yb 3+ 、Lu 3+ ,Ge 4+ Sn 4+ 、Te 4 + , Pt 4+ , Ba 2+ , Pb 2+ , Ca 2+ , Sr 2+ 、Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ Cr 2+ Mg 2+ , Mn 2+ 、Cd 2+ , Nb 5+ 、Mo 5+ , W 6+ One or more of .

[0011] In one embodiment, the second metal element includes Fe 3+ , Ga 3+ ,La 3+ 、Ce 3+ 、Dy 3+ , Ca 2+ Mg 2+ , Mn 2+ , Nb 5+ 、Mo 5+ One or more of .

[0012] In a second aspect, the present invention provides a method for preparing the solid electrolyte material, comprising the following steps:

[0013] LiCl, Li2S, the chloride of the first metal element and the chloride of the second metal element are mixed and ball-milled according to a stoichiometric ratio to obtain a solid electrolyte material.

[0014] In one embodiment, the ball milling is performed at a rotation speed of 600 rpm to 1000 rpm; and / or, the ball milling time is 2 h to 72 h.

[0015] In a third aspect, the present invention further provides a solid-state battery, comprising a positive electrode plate, a negative electrode plate and a solid-state electrolyte, wherein the solid-state electrolyte comprises the solid-state electrolyte material.

[0016] In the above-mentioned solid electrolyte material, the first metal element can form a crystal structure framework that conducts lithium ions. By blending the first metal element and the second metal element, the ionic conductivity of the solid electrolyte material is effectively improved, and the ionic conductivity of the solid electrolyte material is further improved by adjusting the ratio of the first metal element and the second metal element. In addition, the deformation capacity of the solid electrolyte material can be increased by doping with the S element, which is conducive to ball milling to form a solid electrolyte with high ionic conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] FIG. 1 is a schematic diagram of a method for preparing a solid electrolyte material according to one embodiment. DETAILED DESCRIPTION

[0018] References to embodiments of the present application will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0019] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features, and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.

[0020] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0021] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0022] If there is no special description, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. If there is no special description, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.

[0023] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, "include" and "comprising" may represent that other components not listed may also be included or only listed components may be included or only listed components may be included.

[0024] The present application provides a solid electrolyte material, the general formula of which is Li a M m N n Cl b S c , wherein M is the first metal element, N is the second metal element; 1<a<5, 0.3<m+n<2, b+2c=a+m×d+n×e, d is the valence of the first metal element, and e is the valence of the second metal element.

[0025] In the general formula, the valence of the Li element is +1, the valence of the M element is d, the valence of the N element is e, the valence of the Cl element is -1, and the valence of the sulfur element is -2.

[0026] As in Li 2.3 Zr 0.7 Fe 0.3 Cl5S 0.5 In the equation, the value of a is 2.3, the value of b is 5, and the value of c is 0.5; the first metal element M is Zr, the value of m is 0.7, and the valence state of Zr is +4, then the value of d is 4; the second metal element N is Fe, the value of n is 0.3, and the valence state of Fe is +3, then the value of e is 3. The value of m+n is 1, which is between 0.3 and 2. At this time, b+2c=5+2×0.5= ​​a+m×d+n×e=2.3+0.7×4+0.3×3=6.

[0027] As in Li 2.7 Zr 0.3Fe 0.7 Cl5S 0.5 In the equation, the value of a is 2.7, the value of b is 5, and the value of c is 0.5; the first metal element M is Zr, the value of m is 0.3; the second metal element N is Fe, and the value of n is 0.7. In this case, b+2c=5+2×0.5= ​​a+m×d+n×e=2.7+0.3×4+0.7×3=6.

[0028] The first metal element is used to form a crystal structure framework that conducts lithium ions. By mixing the first metal element and the second metal element, an amorphous twin phase can be formed. It can be understood that the twin phase here is a first crystal phase including elements Li, M, Cl, S and a second crystal phase including elements Li, N, Cl, S.

[0029] When the twin phases coexist, the solid electrolyte has a higher degree of amorphization than the single crystal phase. For halide solid electrolytes, the degree of amorphization is closely related to ionic conductivity, specifically, the higher the degree of amorphization, the higher the ionic conductivity. In addition, the deformation capacity of the solid electrolyte material is increased by S doping, which is conducive to the coexistence of two phases.

[0030] It should be noted that the above is only a possible speculation on the mechanism and does not constitute a limitation on the scope of protection.

[0031] Optionally, m+n=1, and the value range of m is 0.3~0.7. For example, the value of m can be 0.3, 0.35, 0.40, 0.45, 0.5, 0.55, 0.6, 0.65, or 0.7, and correspondingly, the value of n is 0.7, 0.65, 0.6, 0.55, 0.5, 0.45, 0.4, 0.35 or 0.3, or a range value between any two of the above. Within this range, the ionic conductivity of the halide solid electrolyte is the largest, and the possible reason is that within this range, the proportion of the two-phase coexistence area is larger.

[0032] Optionally, c has a value range of 0.4 to 1. For example, the value of c can be 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95 or 1, or a range between any two of the above. When c < 0.4, the electrolyte has a high Young's modulus and a hard texture, and it is difficult to form a two-phase coexistence zone at the microscopic level, resulting in two-phase separation and low conductivity; when c > 1, more raw materials remain, it is difficult to form a crystal phase, and the conductivity is low.

[0033] Optionally, the first metal element includes Zr 4+ 、Ti 4+ , Hf 4+ 、Al 3+ , Y3+ Sc 3+ 、In 3+ 、Eu 3+ Preferably, the first metal element includes Zr 4+ , Y 3+ 、In 3+ One or more of .

[0034] Optionally, the second metal element includes Fe 3+ 、V 3+ , Ga 3+ 、Ru 3+ , Rh 3+ 、Bi 3+ 、Au 3+ , Ir 3+ 、Re 3+ ,La 3+ 、Ce 3 + , Pr 3+ 、Nd 3+ 、Sm 3+ , Gd 3+ , Tb 3+ 、Dy 3+ 、Ho 3+ , Er 3+ 、Tm 3+ , Yb 3+ 、Lu 3+ ,Ge 4+ Sn 4+ 、Te 4+ , Pt 4+ , Ba 2+ , Pb 2+ , Ca 2+ , Sr 2+ 、Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ Cr 2+ Mg 2+ , Mn 2+ 、Cd 2+ , Nb 5+ 、Mo 5+ , W 6+ Preferably, the second metal element includes Fe 3+ , Ga 3+ ,La 3+ 、Ce 3+ 、Dy 3+ , Ca 2+ Mg 2+ , Mn 2+ , Nb 5+、Mo 5+ One or more of .

[0035] The present application also provides a method for preparing the above-mentioned solid electrolyte material, comprising: mixing LiCl, Li2S, a chloride of a first metal element and a chloride of a second metal element and ball milling them according to a stoichiometric ratio to obtain a solid electrolyte material. Optionally, the chloride of the first metal element is represented by FCl f , the chloride of the second metal element is represented by GCl g , wherein F represents the first metal element, and f represents the valence state of the first metal element. For example, if the first metal element is Zr and the valence is +4, then f is 4. G represents the second metal element, and g represents the valence state of the second metal element. For example, if the second metal element is Fe and the valence is +3, then g is 3.

[0036] Optionally, referring to FIG. 1 , in one implementation, the method for preparing the solid electrolyte material includes the following steps S12 and S14:

[0037] S12, adding LiCl, Li2S, chloride of the first metal element and chloride of the second metal element into a ball mill according to a stoichiometric ratio, adding ball mill beads and sealing.

[0038] S14, ball milling to obtain a solid electrolyte material.

[0039] Optionally, the process of mixing LiCl, Li2S, the chloride of the first metal element and the chloride of the second metal element can be carried out in a glove box, wherein the water content in the glove box satisfies less than 10 ppm and the oxygen content satisfies less than 50 ppm. Within this range, the raw materials can be kept dry and the purity of the raw materials can be ensured.

[0040] Alternatively, the ball milling process can be carried out in a ball milling device, wherein LiCl, Li2S, the chloride of the first metal element and the chloride of the second metal element are added to the ball milling device according to the stoichiometric ratio, ball milling beads are added and sealed, and then ball milling is carried out. Alternatively, the ball milling device can be a ball milling jar. Alternatively, the grinding aid can be a mixture of one or more of water, alcohol, acetone, benzene and ether.

[0041] Optionally, the mass ratio of the ball milling beads to the raw materials is (15:1) to (60:1), and the mass of the raw materials refers to the total mass of LiCl, Li2S, the chloride of the first metal element, and the chloride of the second metal element. For example, the mass ratio of the ball milling beads to the raw materials can be 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 50:1, 55:1 or 60:1, or a range between any two of the above. If the ratio of the ball milling beads to the raw materials is less than 15:1, the number of ball milling beads is too small, resulting in reduced grinding capacity, making the ball milling process slow and inefficient, and the raw materials cannot be fully stressed, resulting in uneven ball milling, and uneven final particle size distribution, affecting conductivity. If the ratio of the ball milling beads to the raw materials is greater than 60:1, there are too many ball milling beads, and more energy is consumed during the ball milling process to drive a large number of ball milling beads to move, which increases energy consumption, and causes the raw materials to be unable to obtain sufficient reaction space, resulting in uneven stirring, uneven final particle size distribution, and even incomplete reaction. Preferably, the mass ratio of ball milling beads to raw materials is (30:1) to (45:1).

[0042] The present application does not limit the material of the ball mill and the ball mill beads. All ball mills and ball mill beads that can be used for the preparation of halide solid electrolytes in the art can be used in the present application. For example, the ball mill and the ball mill beads are made of zirconium dioxide.

[0043] Optionally, the rotation speed of the ball milling device during ball milling is 600 rpm~1000 rpm. For example, the rotation speed of the ball milling device can be 600 rpm, 650 rpm, 700 rpm, 720 rpm, 750 rpm, 800 rpm, 850 rpm, 900 rpm, 950 rpm or 1000 rpm, or a range value between any two of the above. If the rotation speed is less than 600 rpm, the raw material particles are not fully ground, the probability of intermolecular collision is reduced, and two-phase coexistence cannot be formed. If the rotation speed is greater than 1000 rpm, excessive shear force is generated, and the raw material may undergo structural changes during the ball milling process, resulting in quality degradation. Preferably, the rotation speed of the ball milling device is 700 rpm~900 rpm. More preferably, the rotation speed of the ball milling device is 720 rpm~750rpm.

[0044] Optionally, the ball milling time is 2 h to 72 h. For example, the ball milling time can be 2 h, 6 h, 12 h, 18 h, 24 h, 32 h, 36 h, 40 h, 48 h, 60 h, 66 h or 72 h, or a range between any two of the above. If the ball milling time is less than 2 h, the reaction time is too long and the crystalline phase cannot be formed. If the ball milling time is greater than 72 h, on the one hand, the ball milling time is too long and the energy consumption is increased, resulting in an increase in production costs. On the other hand, the excessive ball milling time may cause the raw material particles to be over-refined, affecting the phase formation. Preferably, the ball milling time is 12 h to 36 h.

[0045] The present application also provides a solid-state battery, the solid-state battery comprising a positive electrode sheet, a negative electrode sheet and a solid-state electrolyte, the solid-state electrolyte comprising the above-mentioned solid-state electrolyte material. The solid-state battery can be a semi-solid-state battery or a fully solid-state battery.

[0046] Optionally, the positive electrode sheet includes a positive electrode active material layer and a positive electrode current collector, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes LiMn2O4, LiFePO4, LiCoO2, LiNi 0.5 MnO4 or LiCoMnO4 or a combination of them.

[0047] Optionally, the negative electrode plate includes a negative electrode active material layer and a negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes one or more of artificial graphite, natural graphite, soft carbon, hard carbon, silicon, silicon carbon, silicon oxygen, and lithium titanate.

[0048] In addition, the present application also provides an electrical device, which includes at least one of the solid-state batteries provided in the present application. The solid-state battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0049] As an electric device, a solid-state battery can be selected according to its use requirements. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the electric device's requirements for high power and high energy density of solid-state batteries, a battery pack or a battery module can be used.

[0050] Another example device may be a mobile phone, a tablet computer, a laptop computer, etc. Such a device is usually required to be thin and light, and a solid-state battery may be used as a power source.

[0051] The following are specific embodiments.

[0052] Example 1

[0053] In this embodiment, the structural formula of the solid electrolyte material is Li 2.3 Zr 0.7 Fe 0.3 Cl5S 0.5 The value of a is 2.3, the value of b is 5, and the value of c is 0.5; the first metal element M is Zr, and the value of m is 0.7; the second metal element N is Fe, and the value of n is 0.3; the molar ratio of the two is 0.7:0.3.

[0054] Preparation method: 1) Add LiCl, Li2S, ZrCl4, and FeCl3 into a ball mill according to the stoichiometric ratio, add ball milling beads and seal; 2) ball mill to obtain a solid electrolyte material.

[0055] The mass ratio of ball milling beads to raw materials is 40:1; the rotation speed of the ball milling device is 750 rpm; and the ball milling time is 20 h.

[0056] Example 2

[0057] In this embodiment, the structural formula of the solid electrolyte material is Li 2.7 Zr 0.3 Fe 0.7 Cl5S 0.5 The difference from Example 1 is that the molar ratio of the first metal element to the second metal element is 0.3:0.7, that is, m is 0.3; the value of a is 2.7. The other technical features are the same.

[0058] Example 3

[0059] In this embodiment, the structural formula of the solid electrolyte material is Li 2.5 Zr 0.5 Fe 0.5 Cl5S 0.5 The difference from Example 1 is that the molar ratio of the first metal element to the second metal element is 0.5:0.5, that is, m is 0.5; the value of a is 2.5. The other technical features are the same.

[0060] Example 4

[0061] In this embodiment, the structural formula of the solid electrolyte material is Li 2.3 Zr 0.7 Fe 0.3 Cl 4.6 S 0.7 The difference from Example 1 is that the value of b is 4.6 and the value of c is 0.7; the other technical features are the same.

[0062] Example 5

[0063] In this embodiment, the structural formula of the solid electrolyte material is Li 2.3 Zr 0.7 Fe 0.3 Cl 4.2 S 0.9 The difference from Example 1 is that the value of b is 4.2, and the value of c is 0.9; the other technical features are the same.

[0064] Example 6

[0065] The difference from Example 1 is that the rotation speed of the ball mill is 600 rpm; the other technical features are the same.

[0066] Example 7

[0067] In this embodiment, the structural formula of the solid electrolyte material is Li3Dy 0.7 Y 0.3 Cl5S 0.5 The difference from Example 1 is that the first metal element is different, Dy is selected, and the chloride of the second metal element is DyCl3; the second metal element is different, Y is selected, and the chloride of the first metal element is YCl3; the value of a is different, which is 3. The other technical features are the same.

[0068] Example 8

[0069] In this embodiment, the structural formula of the solid electrolyte material is Li 3.3 In 0.7 Mg 0.3 Cl5S 0.5 The difference from Example 1 is that the first metal element is different, In is selected, and the chloride of the first metal is InCl3; the second metal element is different, Mg is selected, and the chloride of the second metal element is MgCl2; the value of a is different, which is 3.3. The other technical features are the same.

[0070] Example 9

[0071] The difference from Example 1 is that the structural formula of the solid electrolyte material is Li 2.3 Zr 0.7 Fe 0.3 Cl 5.6 S 0.2 . c is less than 0.4, c is 0.2, b is 5.6, and the other technical features are the same.

[0072] Example 10

[0073] The difference from Example 1 is that the structural formula of the solid electrolyte material is: Li 2.3 Zr 0.7 Fe 0.3 Cl 3.8S 1.1 . c is greater than 1, c is 1.1, b is 3.8; the other technical features are the same.

[0074] Embodiment 11

[0075] The difference from Example 1 is that the structural formula of the solid electrolyte material is Li 2.8 Zr 0.2 Fe 0.8 Cl5S 0.5 The value of m is 0.2, and the value of a is 2.8. The other technical features are the same.

[0076] The difference between Example 12 and Example 1 is that the structural formula of the solid electrolyte material is Li 2.2 Zr 0.8 Fe 0.2 Cl5S 0.5 The value of m is 0.8, and the value of a is 2.2. The other technical features are the same.

[0077] Comparative Example 1

[0078] In this comparative example, the structural formula of the solid electrolyte material is Li2ZrCl6. The preparation method is the same.

[0079] Comparative Example 2

[0080] The difference from Example 1 is that the structural formula of the solid electrolyte material is Li2ZrCl5S 0.5 . The preparation method is the same.

[0081] Comparative Example 3

[0082] The difference from Example 1 is that the structural formula of the solid electrolyte material is Li 2.3 Zr 0.7 Fe 0.3 Cl6. The preparation method is the same.

[0083] The general formula compounds and process parameters of Examples 1 to 12 and Comparative Examples 1 to 3 are listed in Table 1, wherein the ball-to-material ratio refers to the mass ratio of ball milling beads to raw materials.

[0084] Table 1

[0085]

[0086] The solid electrolyte materials prepared in Examples 1 to 12 and Comparative Examples 1 to 3 were subjected to ion conductivity tests, and solid batteries were prepared using the prepared solid electrolyte materials for battery capacity tests. The test results are shown in Table 2 below.

[0087] Among them, the ionic conductivity test method of the solid electrolyte is: at room temperature, take the solid electrolyte obtained in the embodiment and the comparative example, prepare it into a solid electrolyte membrane, connect it to the electrochemical workstation respectively, and perform an initial impedance test, and calculate the final ionic conductivity according to the formula σ=I / (AR). The data are collected as shown in Table 1; wherein σ is the conductivity, the unit is S / cm, I is the average thickness of the solid electrolyte membrane, the unit is cm; A is the area of ​​the solid electrolyte membrane, the unit is cm2; R is the body impedance of the solid electrolyte membrane, the unit is Ω.

[0088] The preparation method of solid-state battery is (including positive electrode material and negative electrode material):

[0089] 1) Positive electrode: The positive electrode active material LiCoO2, the conductive agent conductive carbon black, the binder PTFE and the solid electrolyte are mixed in a ratio of 90:3:2:5 to prepare a composite positive electrode. The type of the solid electrolyte is the same as that of the corresponding embodiment and comparative example;

[0090] 2) Metal lithium is used as the negative electrode;

[0091] 3) Selecting the solid electrolyte powders in the corresponding embodiments and comparative examples, and pressing them to form a solid electrolyte membrane;

[0092] 4) Assemble the positive electrode, solid electrolyte membrane, and negative electrode into a battery in sequence.

[0093] The battery capacity test method of the solid-state battery is as follows: The solid-state batteries prepared in the above embodiments and comparative examples were subjected to capacity tests, and discharged at 0.1C at a temperature of 25°C±2°C to a termination voltage of 2.7V.

[0094] Table 2

[0095]

[0096] As can be seen from Table 2 above, the first metal element of the solid electrolyte material prepared in Examples 1 to 12 forms a crystal structure framework that conducts lithium ions, and the first metal element and the second metal element are blended to effectively improve the ionic conductivity of the solid electrolyte material and increase the ionic conductivity of the solid electrolyte material. In addition, doping with the S element is beneficial to further improve the ionic conductivity.

[0097] The solid electrolyte of Comparative Example 1 includes only one metal element and does not have the S element. The ionic conductivity and battery capacity of the solid electrolyte are significantly smaller than those of Examples 1 to 12.

[0098] The solid electrolyte of Comparative Example 2 includes only one metal element, and its ion conductivity is lower than that of the solid electrolytes of Examples 1 to 12. The possible reason is that the solid electrolyte prepared in Comparative Example 2 is a single phase, while the solid electrolytes prepared in Examples 1 to 12 include a twin phase, which is beneficial to improving the ion conductivity.

[0099] Compared with Comparative Example 1, Comparative Example 2 has S doping, which increases its ion conductivity and battery capacity, proving that S doping is beneficial to crystal phase stability.

[0100] Compared with Example 1, Comparative Example 3 does not contain the S element, which leads to a decrease in ionic conductivity and battery capacity, proving that S doping further improves ionic conductivity. The possible reason is that the addition of raw materials containing the S element to the blend is beneficial to increasing the deformation ability of the solid electrolyte, facilitating the ball milling to form a solid electrolyte with higher ionic conductivity, and facilitating the formation of a twin phase.

[0101] Compared with Example 1, Example 9 has an S element doping amount c value less than 1, resulting in reduced ion conductivity and battery capacity, proving that the S element doping amount cannot be too small, otherwise it will cause separation of the two crystalline phases. Compared with Example 1, Example 10 has an S element doping amount c value greater than 1, resulting in reduced ion conductivity and battery capacity, proving that the S element doping amount cannot be too large, otherwise it will cause difficulty in phase formation.

[0102] Compared with Example 1, the molar ratio of the first metal element to the second metal element in Example 11 is 0.2:0.8, and the value of m is 0.2. Compared with Example 1, the molar ratio of the first metal element to the second metal element in Example 12 is 0.8:0.2, and the value of m is 0.8. Both Example 11 and Example 12 lead to a decrease in ionic conductivity and a decrease in battery capacity, which proves that when the value of m is in the range of 0.3~0.7, it is beneficial to improve the ionic conductivity of the halide solid electrolyte. The possible reason is that when the value of m is in the range of 0.3~0.7, the proportion of the two-phase coexistence area in the solid electrolyte is larger.

[0103] The above is only a possible speculation on the mechanism and does not constitute a limitation on the scope of protection.

[0104] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0105] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A solid electrolyte material, characterized in that: The general formula of the solid electrolyte material is Li a M m N n Cl b S c , wherein M is the first metal element, N is the second metal element; 1<a<5, 0.3<m+n<2, b+2c=a+m×d+n×e, d is the valence of the first metal element, and e is the valence of the second metal element.

2. The solid electrolyte material according to claim 1, characterized in that m+n=1, the value range of m is 0.3~0.

7.

3. The solid electrolyte material according to claim 1, characterized in that The value range of c is 0.4~1.

4. The solid electrolyte material according to claim 1, characterized in that The first metal element includes Zr 4+ 、Ti 4+ , Hf 4+ 、Al 3+ , Y 3+ Sc 3+ 、In 3+ 、Eu 3+ One or more of .

5. The solid electrolyte material according to claim 4, characterized in that The first metal element includes Zr 4+ , Y 3 + 、In 3+ One or more of .

6. The solid electrolyte material according to claim 1, characterized in that The second metal element includes Fe 3+ 、V 3 + , Ga 3+ 、Ru 3+ , Rh 3+ 、Bi 3+ 、Au 3+ , Ir 3+ 、Re 3+ ,La 3+ 、Ce 3+ , Pr 3+ 、Nd 3+ 、Sm 3+ , Gd 3+ , Tb 3+ 、Dy 3+ 、Ho 3+ , Er 3+ 、Tm 3+ , Yb 3+ 、Lu 3+ ,Ge 4+ Sn 4+ 、Te 4+ , Pt 4+ , Ba 2+ , Pb 2+ , Ca 2+ , Sr 2+ 、Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ Cr 2+ Mg 2+ , Mn 2 + 、Cd 2+ , Nb 5+ 、Mo 5+ , W 6+ One or more of .

7. The solid electrolyte material according to claim 6, characterized in that The second metal element includes Fe 3+ , Ga 3+ ,La 3+ 、Ce 3+ 、Dy 3+ , Ca 2+ Mg 2+ , Mn 2+ , Nb 5+ 、Mo 5+ One or more of .

8. A method for preparing a solid electrolyte material according to any one of claims 1 to 7, characterized in that: The following steps are involved: LiCl, Li2S, the chloride of the first metal element and the chloride of the second metal element are mixed and ball-milled according to a stoichiometric ratio to obtain a solid electrolyte material.

9. The method according to claim 8, characterized in that The ball milling is performed at a rotation speed of 600 rpm to 1000 rpm; and / or, the ball milling time is 2 h to 72 h.

10. A solid-state battery, characterized in that: The solid-state battery comprises a positive electrode sheet, a negative electrode sheet and a solid electrolyte, and the solid electrolyte comprises the solid electrolyte material according to any one of claims 1 to 7.